The effects of health insurance and physical exercise participation on life satisfaction of older people in China—Based on CHNS panel data from 2006 to 2015 - Luo, Lin; Zeng, Xiaojin; Wang, Xiangfei (Frontiers in Public Health, 2022)
Background In China, the problem of aging population has become more and more serious. The factors influencing life satisfaction of older people are becoming a significant issue. This study explores the effects of health insurance and physical exercise on life satisfaction of older people in China. Method This study used an unbalanced panel dataset (n = 6,393, T = 4) of older adults aged 60–80 years from the 2006 to 2015 China Health and Nutrition Survey (CHNS). A panel ordered logistic regression model was developed to examine the effects of health insurance and physical exercise on older people' life satisfaction. Mediation tests were used to examine the mediating role of physical exercise in the effect of health insurance on life satisfaction of older people. Result Life satisfaction of older people was positively associated with participation in health insurance (OR = 1.439) and physical exercise (OR = 1.033). Participation in government health insurance, urban employee health insurance (UEBMI), new rural cooperative health insurance (NRCMI), and other commercial health insurance all have positive effects on life satisfaction of older people. Physical exercise plays a masking role in the effect of health insurance on life satisfaction of older people. Conclusion Participation in health insurance and physical exercise are important means to promote life satisfaction among older people. Physical exercise affects the impact of health insurance on older people's life satisfaction.